TANTANGAN MAHASISWA PENDIDIKAN TEKNIK MESIN DALAM MENJAGA KONSISTENSI DISIPLIN KEISLAMAN DAN PENDIDIKAN - Farrij Rizqi Fadhillah; Muhammad Wildan Firdaus; Raihan Musthofa Zahrani; Jenuri (Indonesian Journal of Islamic Studies (IJIS), 2026)
Mechanical Engineering Education (PTM) demands logical precision and mastery of high technology, creating an intensive academic burden for students. This condition often leads to an invisible dichotomy between "campus obligations" and "religious obligations," where Muslim PTM students struggle to maintain consistency in Islamic discipline, such as five-times prayer and moral development. This research aims to explore the challenges faced by Mechanical Engineering Education (PTM) students in maintaining Islamic discipline amid high academic demands. The method used is a Literature Review with a critical approach, which collects and analyzes various literature to identify gaps in knowledge. The main findings reveal that the primary challenges include the decline of ethical values such as honesty due to the impact of social changes and technological advancements, the risk of weakened character caused by the influence of global secular culture, and the heavy curriculum burden that leads to mental and physical exhaustion as well as conflicts between academic schedules and religious obligations. Furthermore, students' excessive focus on achieving high GPA and technical skills often neglects moral development, compounded by the lack of integration of the ta’dib concept and insufficient support from social environments that can enforce discipline. Therefore, a holistic and integrated solution is necessary to make Islamic ethics the foundation of academic and professional behavior,balancing technical expertise and spiritual aspects so that PTM students can become competent individuals with strong Islamic character.